$$\int_0^{\pi/4}\log\left(\tan{x}\right)\ dx$$ My turn : $$I=\int_0^{\pi/4}\log\left(\sin{x}\right)-\log\left(\cos{x}\right)\ dx$$ $$I_1=\int_0^{\pi/4}\log\left(\sin{x}\right)\ dx$$ let $$u=2x$$ $$I_1=\frac{1}{2}\int_0^{\pi/2}\log\left(\sin{\frac{u}{2}}\right)\ du$$ But i could not evaluate the last integral ?

  • 3
    $\begingroup$ The integral of $\ln(\sin(x))$ is not expressible in terms of elementary functions. Yet by a mere knowledge of special functions, you can easily find that $$\int \ln(\sin(x))\ \text{d}x = \frac{1}{2} i \left(x^2+\text{Li}_2\left(e^{2 i x}\right)\right)-x \log \left(1-e^{2 i x}\right)+x \log (\sin (x))$$ Where $\text{Li}_n$ defines the Poly-Logarithm special function. $\endgroup$ – Turing Jun 11 '18 at 13:49
  • $\begingroup$ Does it work with $$\log\left(\cos{x}\right)$$ $\endgroup$ – Hussien Mohamed Jun 11 '18 at 14:36
  • $\begingroup$ It does. In particular: $$\int\ln\cos(x))\ \text{d}x = \frac{1}{2} i \text{Li}_2\left(-e^{2 i x}\right)+\frac{i x^2}{2}-x \log \left(1+e^{2 i x}\right)+x \log (\cos (x))$$ $\endgroup$ – Turing Jun 12 '18 at 7:32

Under $\tan x\to x$, one has \begin{eqnarray} &&\int_0^{\pi/4}\ln(\tan x)dx\\ &=&\int_0^1\frac{\ln x}{1+x^2}dx\\ &=&\int_0^1\ln x\sum_{n=0}^\infty(-1)^nx^{2n}dx\\ &=&-\sum_{n=0}^\infty\int_0^1(-1)^nx^{2n}\ln xdx\\ &=&-\sum_{n=0}^\infty(-1)^n\frac{1}{(2n+1)^2}\\ &=&-C \end{eqnarray} where $C$ is the Catalan constant.


Another way is to use the Fourier expansion of $\log\sin x$ and $\log\cos x$ and integrate the expression term-wise. Since

$$\begin{align*}\log\cos x & =\sum\limits_{k\geq1}(-1)^{k-1}\frac {\cos 2kx}k-\log 2\\\log\sin x & =-\sum\limits_{k\geq1}\frac {\cos 2kx}k-\log 2\end{align*}$$

Therefore$$\begin{align*}I & =\int\limits_0^{\pi/4}dx\,\log\tan x\\ & =\int\limits_0^{\pi/4}dx\,\log\sin x-\int\limits_0^{\pi/4}dx\,\log\cos x\\ & =-\sum\limits_{k\geq1}\int\limits_0^{\pi/4}dx\,\frac {\cos 2kx}k+\sum\limits_{k\geq1}\int\limits_0^{\pi/4}dx\, (-1)^k\frac {\cos 2kx}k\end{align*}$$

Now integrate within the limits to get$$\begin{align*}I & =\frac 12\sum\limits_{k\geq1}\frac {(-1)^k\sin\left(\frac {\pi k}2\right)}{k^2}-\frac 12\sum\limits_{k\geq1}\frac {\sin\left(\frac {\pi k}2\right)}{k^2}\\ & =-\frac 12\sum\limits_{k\geq1}\frac {(-1)^k}{(2k-1)^2}-\frac 12\sum\limits_{k\geq1}\frac {(-1)^k}{(2k-1)^2}\\ & =-G\end{align*}$$Where $G$ is Catalan's Constant.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.